2012
DOI: 10.1007/s10711-012-9719-z
|View full text |Cite
|
Sign up to set email alerts
|

On the curvature on G-manifolds with finitely many non-principal orbits

Abstract: We investigate the cuvature of invariant metrics on G-manifolds with finitely many non-principal orbits. We prove existence results for metrics of positive Ricci curvature and non-negative sectional curvature, and discuss some families of examples to which these existence results apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In [BW2] Theorems 5 and 6, it is shown that the families in Examples 1.6 and 1.7 below both contain infinitely many homotopy types.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In [BW2] Theorems 5 and 6, it is shown that the families in Examples 1.6 and 1.7 below both contain infinitely many homotopy types.…”
mentioning
confidence: 99%
“…In [BW2] a general existence result is established for positive Ricci curvature metrics on G-manifolds with finitely many non-principal orbits (see Proposition 1.11 below). Using this result, many Ricci positive examples were presented.…”
mentioning
confidence: 99%
See 3 more Smart Citations